Psychological Analysis of Emily Grierson in Short Story A Rose for Emily by William Faulkner - Santoso, Gaby Kumala Dewi; Putra Yadnya, Ida Bagus; Alit Ida Setianingsih, Ni Ketut (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 21 No 2 (2021), 2021)
Literature is something that always accompanied our life, they may be fiction or non-fiction. However, both have the same intrinsic and extrinsic elements. One of the intrinsic elements is character. The characters in a story are an intriguing thing, each characters have different personality. The personality created by internal and external factors that influence the psychological condition of the character. This study entitled Psychological Analysis of Emily Grierson in Short Story A Rose for Emily by William Faulkner, mainly discuss about Emily psychological condition. Specifically, on her living environment’s influence on her psychology also her psychological reason in killing and keeping her lover and/or husband. This study used a descriptive qualitative method in analyzing the collected data. The theory used is theories of personality from Feist & Feist (2008), specifically Karen Horney’s psychoanalytic social theory. There is also historical background theory used to determines the living environment’s influence. The result of this study is Emily living environment greatly influence her psychological condition, especially due to her identity as a fallen aristocratic lady and her family’s lack of man to protect her. As for her reason for killing and keeping her lover and/or husband, it is because of her fear being alone and needing other people in her live that she approaches him and end in her feeling that he is hers. Thus, him leaving her, end in the tragedy of him losing his life and being keep as a means to satisfy her possessive desire.